Interplay between grain boundary segregation and electrical resistivity in dilute nanocrystalline Cu alloys. (October 2016) - Kim, Gyuseok; Chai, Xuzhao; Yu, Le; Cheng, Xuemei; Gianola, Daniel S.
Abstract: The relationships between microstructure, controlled by alloying elements prone to grain boundary segregation, and electrical resistivity in sputtered nanocrystalline Cu were investigated. We find a non-monotonic dependence of the mean grain size on solute concentration for both Cu-Nb and Cu-Fe dilute alloys, with a concentration regime where the grain size increases over that of pure Cu before refining with further alloying. The electrical resistivity follows the same trend, suggesting a non-equilibrium processing route that remarkably gives rise to dilute nanocrystalline Cu alloys with lower resistivity, thermal stability, and enhanced mechanical properties relative to their pure nanocrystalline counterpart. Graphical abstract: